Wastepaper Modernism - Rosenberg, Joseph Elkanah (Oxford University Press, 2021)
Wastepaper Modernism traces how 20th-century writers imagined the fate of paper at the dawn of a new media age.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Fiction-20th century-History and criticism; Modernism (Literature)-History; Paper in literature